Evaluation of Professional Qualification of the Personnel Authorized for Work with Pathogenic Biological Agents of I-II Groups - A. V. Boiko; T. A. Malyukova; L. A. Tikhomirova; Z. S. Yusupova; M. N. Lyapin; A. V. Toporkov (Проблемы особо опасных инфекций, 2011)
Presented is the algorithm of assessment of the level of professional qualification of the personnel authorized for work with pathogenic biological agents of I-II groups, developed for the first time. Determined are the essence, requirements for organization and order of assessment of the indices that predict the presence of occupational knowledge and skills necessary for safe, high-quality and effective execution of professional duties.